MENINGKATKAN MINAT BELAJAR SEJARAH SISWA MELALUI MODEL QUANTUM TEACHING KELAS XI IPA SMA NEGERI 9 PEKANBARU (JS (JURNAL SEKOLAH), 2019)
Abstract: Increasing Interest in Learning History of Students Through Quantum Teaching Model Class XI IPA Senior High School 9 Pekanbaru. The purpose of this research is to determine the application of the Quantum Teaching model to increase students' interest in historical subjects. This type of research is classroom action research. The subject of this study was students of class XI Natural Science 4. Data collection techniques and research instruments were using observation techniques using observation sheets of student learning interest. The results of this study indicate that the Quantum Teaching model can increase student learning interest where in each cycle there is an increase in student learning activities from 38.73% at initial observation to 66.97% in the first cycle and an increase of 85.96% in the second cycle. This shows the Quantum Teaching model can increase students' interest in learning history subjects.Keywords: Learning Interest, Quantum Teaching Model, History LearningAbstrak: Meningkatkan Minat Belajar Sejarah Siswa Melalui Model Quantum Teaching Kelas XI IPA SMA Negeri 9 Pekanbaru. Tujuan dari penelitian ini adalah untuk menentukan penerapan model Quantum Teaching untuk meningkatkan minat belajar siswa dalam mata pelajaran sejarah. Jenis penelitian ini adalah penelitian tindakan kelas. Subjek penelitian ini adalah siswa kelas XI IPA 4. Teknik pengumpulan data dan instrumen penelitian adalah menggunakan teknik observasi menggunakan lembar observasi minat belajar siswa. Hasil penelitian ini menunjukkan bahwa model Quantum Teaching dapat meningkatkan minat belajar siswa di mana pada setiap siklus ada peningkatan aktivitas belajar siswa dari 38,73% pada observasi awal menjadi 66,97% pada siklus pertama dan terjadi peningkatan 85,96% di siklus kedua. Hal ini menunjukkan model Quantum Teaching dapat meningkatkan minat siswa dalam mempelajari mata pelajaran sejarah.Kata kunci: Minat Belajar, Model Quantum Teaching, Pelajaran Sejarah